2021
DOI: 10.1038/s41551-021-00745-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning models for the detection and incidence prediction of chronic kidney disease and type 2 diabetes from retinal fundus images

Abstract: Regular health screening plays a crucial role in the early detection of common chronic diseases and prevention of their progression. An AI system capable of recapitulating early disease detection, staging and incidence prediction would help to improve healthcare access and delivery, particularly in resource-poor or remote settings. Using a total of 115,344 retinal fundus photographs from 57,672 patients (with data split into mutually exclusive training, internal testing, and external validation sets), we first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
145
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(173 citation statements)
references
References 44 publications
0
145
4
Order By: Relevance
“…In addition, due to the low medical and economic resources in underdeveloped and remote areas, the ophthalmologist to patient ratio is low, leading to delayed diagnosis and deterioration of MGD in some patients. For example, in Nigeria, reported physician to patient ratio is as low as 1:2,660 ( 27 ). An efficient and socially effective method for evaluating meibomian gland function is therefore needed urgently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the low medical and economic resources in underdeveloped and remote areas, the ophthalmologist to patient ratio is low, leading to delayed diagnosis and deterioration of MGD in some patients. For example, in Nigeria, reported physician to patient ratio is as low as 1:2,660 ( 27 ). An efficient and socially effective method for evaluating meibomian gland function is therefore needed urgently.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of this finding are relevant as a blood test is currently required to assess this risk. In this area of research, recent studies have highlighted the potential of artificial intelligence (AI) algorithms to identify CKD categories from retinal photographs using existing datasets from DR screening programs [ 41 , 42 ]. However, the performance of these models is not directly comparable to our results for a variety of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that deep learning could diagnose DN based on only six types of IF staining [18]. There have also been studies that predicted systemic conditions and clinical metrics based on fundus photographs, suggesting that deep-learning algorithms can detect subtle associations that are undetectable to human observers [19,20].…”
Section: Of 11mentioning
confidence: 99%